Test Method of Traction and Braking Characteristics for a Novel Urban-rail Traction Motor - HE Bo-jun; JING Hua-bing; XIAO Quan-hua; LIANG Wen-chao; LIANG Jin-cheng (机车电传动)
Based on the analysis of mathematics model for a novel urban-rail traction motor, the operation process of traction motor was researched, the traction and braking characteristics of the motor were analyzed, control method of traction motor was presented, and typical parameters of the traction motor were deducted. With operation controlling method, test of traction and braking characteristics were accomplished to obtain traction & braking parameters and characteristics curves for 190 kW urban-rail AC variable-frequency traction motor by experiment, which accorded with theoretical curves of literature. The traction and braking characteristics of traction motor were also verified by testing results.